Calculation of nonlinear covers deformation with the developed median surface the approached analytical methods - Андрианов, Игорь Васильевич; Мильцын, Анатолий Михайлович; Олевский, Виктор Исаакович; Плетин, Владислав Валентинович (Eastern-European Journal of Enterprise Technologies, 2010)
An analysis of the approximate analytical calculation of the displacements of inhomogeneously loaded shells with developable principal surface by means of modified methods of Adomian's decomposition, homotopy perturbation and the parameter continuation was represented, taking into account the geometric nonlinearity. A generalized summation of the solutions was used based on one-and two-dimensional Pade approximants.